Komunikasi Persuasif Sebagai Teknik Mengajar Guru Dalam Mengatasi Miskonsepsi Siswa RA Al-Badri Jember - Faozan, Bagus Ahmad; Jauhari, Minan; Wazis, Kun (Jayapangus Press, 2024)
Persuasive communication is a communication process that aims to influence, convince, or persuade others to do or believe something. The ultimate goal is to influence the attitudes, beliefs, or behaviors of the target audience. In persuasive communication, the sender of the message uses various strategies, such as logic, emotion, authority, or concrete evidence, to build a strong and convincing argument. The purpose of this study is persuasive communication as a teacher teaching technique in overcoming student misconceptions at RA Al-Badri Jember. The research method used is qualitative descriptive by taking objects at RA Al-Badri Teachers as data to see teacher interactions with students in overcoming misconceptions that occur. The results of this study are misconceptions that often occur in students in reading, writing, and arithmetic, where the teacher in overcoming cannot be separated from the concept of self, mind and society, the teacher brings the concept of himself by emphasizing the same background or the same fate as the students. In the process of persuasive communication, teachers apply persuasive communication techniques to overcome students' misconceptions in the teaching and learning process. The techniques used are association, integration, rewards and settings.